The Emancipation’s Ideology Represented in Hanung Bramantyo’s Film “Habibie Ainun 3”: A Semiotic Approach - Isnaini, Nur Alfiana (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
This is common to represent the life society through the movie show. This article studied the ideology of emancipation that appears through the utterances or behaviors which are performed by the actors in the film entitled Habibie Ainun 3- A film by Hanung Bramantyo. This study has the aim to scrutinize and represent the ideology of emancipation where becomes the representation of society. This study applied qualitative research using the semiotic approach. Moreover, the methodology that is used by the researcher is the annotation step to gather the data and the Semiotic theory by John Fiske (television codes) in investigating the data which has the three levels: a). the reality level, b). the representation level, and c). the ideology level. The results of this study delineated that the utterances and behaviours are divided into two types, and those are bad manner and good manner with the interpretation of each data which covered the ideology of emancipation.